Tweetre: What role can technology play in contemporary theatre? (Itinera, 2017)
This article is a brief, individual review which illustrates some advances that digital technology can foster for theatre. Whether this can be seen as an encroachment or augmentation in this field, there are clear examples of significant opportunities for practitioners who follow the digital route as a means to increase theatrical participation. Concurrent to this, this article will demonstrate the validity of using the principles of game design to consider the potentials offered by digital theatre and indicate possible avenues for future research.